2018
DOI: 10.1097/ncq.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of Nurses and Hospitals With Ventilator-Associated Pneumonia Prevention Guidelines

Abstract: This study was a self-reported cross-sectional survey that investigated nurses' and hospitals' compliance with ventilator-associated pneumonia prevention guidelines and the barriers and factors that affect their level of compliance. A questionnaire was completed by 471 intensive care unit nurses from 16 medical centers in 3 Middle Eastern countries: Jordan, Egypt, and Saudi Arabia. The results show that both nurses and hospitals have insufficient compliance. Previous education, experience, and academic degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(64 citation statements)
references
References 23 publications
1
47
0
16
Order By: Relevance
“…When investigating the replacement of the wound dressing, only 55.1% of the sample reported the correct frequency for changing of the dressing, and 61.9% of nurses reported the utilization of adhesive drapes.Furthermore, concerning barriers of compliance with surgical site infection prevention guidelines, about two thirds of nurses agree that, lack of a professional model, nurses do not have enough time, and some measures for the prevention of surgical site infection are not nurses' responsibilities, are the most barriers facing them with surgical site infection prevention guidelines. Aloush, et al, (2017)[30] their finding were in accordance with our study, as in their study, the Participants reported several barriers that prevented their compliance with the guidelines, especially lack of education, lack of a professional model, and poor integration of research findings in practice. They also stated that, (63%) of the participants, had received no education about the guidelines in their schools.This finding supports the significance of education in the improvement of nurses' compliance, as reported in other studies[40] [41].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…When investigating the replacement of the wound dressing, only 55.1% of the sample reported the correct frequency for changing of the dressing, and 61.9% of nurses reported the utilization of adhesive drapes.Furthermore, concerning barriers of compliance with surgical site infection prevention guidelines, about two thirds of nurses agree that, lack of a professional model, nurses do not have enough time, and some measures for the prevention of surgical site infection are not nurses' responsibilities, are the most barriers facing them with surgical site infection prevention guidelines. Aloush, et al, (2017)[30] their finding were in accordance with our study, as in their study, the Participants reported several barriers that prevented their compliance with the guidelines, especially lack of education, lack of a professional model, and poor integration of research findings in practice. They also stated that, (63%) of the participants, had received no education about the guidelines in their schools.This finding supports the significance of education in the improvement of nurses' compliance, as reported in other studies[40] [41].…”
supporting
confidence: 92%
“…Three quarters (75.0%) of the nurses reported that they never ensure patients bathe or shower, and (77.3%) never limit the number of people and doors being opened, and (69.0%) never check wounds for infection and use standard dressings on primary wounds, moreover, nurses' compliance mean scores were in low level with a mean of 13.01 (SD = 3.00), and majority (84.75%) of the nurses were classified in low compliance, (13.25%) in moderate compliance, and (2%) in high compliance. These findings are similar to other studies such as Aloush., et al, [30], Jahansefat et al, [31], and Narendranath et al, [32], who reported poor compliance among nurses. As well, Alhirish et al, [33] in Egypt, and Rizwan et al, [34] who reported a significant increase in nosocomial infection in Pakistan as a result of poor compliance with infection prevention guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that the knowledge and application levels of VAP initiatives by nurses can be increased with training [17,19,[33][34][35]. In studies where training initiatives for preventing VAP were studied, the level of nurses' knowledge and awareness of VAP, and their compliance levels for the care bundle were increased, and the incidence of VAP was decreased [3,16,18,26]. It was determined in this study that the mean scores at the last measurement in the study and control groups were higher at a statistically significant level.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is emphasized that training health workers, especially nurses, in VAP interventions, and increasing their level of knowledge on this subject, play very important roles [13][14][15]. It is reported, however, that intensive care nurses have low-level or moderate awareness, knowledge, attitude, and harmony about evidence-based practices to prevent VAP [12,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation